Auswärtiger Handel im Jahre 1907 - Deutsches Reich / Statistisches Reichsamt (Berlin : Puttkammer & Mühlbrecht, 1909)
entsäuert
Keywords: Deutsches Reich; Statistik; Seeschifffahrt; Schifffahrt; Güterverkehr